Features of aldosterone antagonists in the treatment of patients with acute myocardial infarction with ST elevation without chronic heart failure and post-MI chronic heart failure with low ejection fraction - V. V. Syvolap; L. V. Lukashenko; S. P. Zhemanyuk; M. P. Gerasko; L. V. Franskyavichene (Zaporožskij Medicinskij Žurnal)
Aim. In order to study the possibilities of aldosterone antagonists in the treatment of patients with acute myocardial infarction with ST elevation without chronic heart failure and post-MI chronic heart failure with low ejection fraction recent researches on this problem were reviewed. The literature data and the results of multicenter randomized controlled trials (RCTs), which will expand not only the understanding of the mechanisms of action of aldosterone receptor antagonists, but also new areas of their application in clinical practice, were analyzed.